Gender Awareness in Islamic Legal Education - Windy Triana; Milah Karmilah (Universitas Islam Negeri Jakarta, 2019)
This article aims at discussing the integration of gender issues in Islamic legal education in Indonesia and Malaysia. In particular, this is to see how gender issues are taught to Islamic law students and integrated into the curricula to instil gender awareness. Based on empirical inquiries in the Department of Family Law of Faculty of Sharia and Law of State Islamic University Syarif Hidayatullah Jakarta and Faculty of Sharia and Law of Academy of Islamic Studies, University of Malaya, this study finds that the attempts to include gender issues in the curricula have been still very limited and insufficient. Courses that directly discuss gender issues and human rights issues are treated merely as elective courses. Except in Jakarta UIN, currently, the specific course on gender becomes a compulsory course. Moreover, the integration of gender discussion into general courses is not easy. This depends on the willingness and awareness of the lecturers to include the discussion. The significant challenge in integrating gender issues in Islamic legal education is related to lecturers and students’ previous norms, values, and ideology. Because of this, the introduction to gender discourse becomes mind-provoking. This study relies on data from the curricula, interviews with faculties’ key figures, and Focus Group Discussion with students from both institutions. Tulisan ini membahas tentang integrase isu gender ke dalam pendidikan hukum Islam di Indonesia dan Malaysia. Fokus penelitian ini adalah untuk melihat bagaimana isu gender diajarkan kepada mahasiswa hukum Islam dan bagaimana isu gender diintegrasikan ke dalam kurikulum untuk menanamkan kesadaran gender. Melalui penelitian empiris di Program Studi Hukum Keluarga, Fakultas Syariah dan Hukum, Universitas Islam Negeri Syarif Hidayatullah Jakarta dan Jabatan Syariah dan Undang-Undang, Akademi Pengajian Islam, Universiti Malaya, kajian ini menemukan bahwa upaya untuk memasukan isu gender dalam kurikulum pendidikan hukum Islam masih sangat terbatas dan belum cukup. Mata kuliah-mata kuliah yang secara langsung membahas isu gender dan hak asasi manusia kebanyakan hanya dijadikan mata kuliah pilihan. Kecuali di UIN Jakarta, baru-baru ini mata kuliah terkait gender menjadi mata kuliah wajib. Selanjutnya, integrasi pembahasan gender ke dalam mata kuliah umum tidak lah mudah. Tantangan paling besar yang dihadapi adalah norma, nilai dan ideologi terdahulu yang dimiliki oleh dosen dan mahasiswa. Hal tersebut menjadikan pengenalan terhadap isu gender menantang bagi pemikiran yang sudah mereka miliki. Data pada kajian ini berasal dari kurikulum, wawancara dengan tokoh-tokoh kunci pada dua fakultas dan Focus Group Discussion dengan mahasiswa dari dua institusi.